Pengaruh Pembelajaran Berbasis Kasus dan Dukungan Teknologi Terhadap Hasil Belajar Mahasiswa Administrasi Perkantoran - Dian Zahwa; Marsofiyati Marsofiyati (Politeknik Kampar, 2024)
Learning is the process of interaction between students, educators, and learning resources within a learning environment. Technology support refers to the use of technology or digital platforms that can help facilitate learning, while learning outcomes are the achievements that students attain after participating in learning activities. The aim of this study is to examine the influence of case-based learning and technology support on students' learning outcomes. This research employs a quantitative approach with a survey method, and the data are analyzed using SPSS. The results indicate that case-based learning does not have a strong influence on students' learning outcomes; however, technology support has a strong influence on learning outcomes. Nevertheless, technology support does not have a strong influence on the success of case-based learning.